An Examination of the Application of Polyurethane-Based Hydrophobic Nanocoatings Inspired by Natural Structures in Extracting Water from Air Humidity - Ashkan Zolriasatein; Sepideh Abdolahzadeh; Negar Motakef kazemi (Journal of Water and Environmental Nanotechnology)
Nowadays, the water shortage has become a severe issue all over the world, especially in some arid and undeveloped areas. Water is a renewable natural resource that can produce freshwater globally. Interestingly, some animals in nature can collect water from fog, which can be the inspiration to develop novel and functional water-collecting materials. A superhydrophobic surface that utilizes no energy has been synthesized from a water-collecting mechanism of the Stenocara beetles back structures. Firstly, this paper reviews the preparation methods of superhydrophobic surface coatings and then it examines patterns inspired by nature. In this paper, hydrophobic nanocoating was manufactured based on polyurethane (PUR) modified by nano-silica. Silica nanoparticles were synthesized via the sol-gel method. Then, silica nanoparticles were dispersed in polyurethane (PU) coatings. In this article, many factors of collecting moisture are evaluated, for example, temperature, pattern placement angle, pattern shape, types of surface patterns, and ambient humidity. Finally, are introduced the optimum situation for absorbing water from the fog.